Sample Frame and Related Sample Design Issues for Surveys of Physicians and Physician Practices. (September 2013) - DiGaetano, Ralph
A sample frame is the listing of the units from which a sample is to be selected. When deciding upon a file to serve as a source for a sample frame for a survey, perhaps the most important consideration is the extent to which the target population will be covered by the frame. However, other issues also come into play such as the accuracy of contact and other information appearing on the file as well as its cost. The American Medical Association Masterfile has long been considered the preferred choice for surveys of physicians, although it does have drawbacks. Here we consider two alternative files, discussing their relative advantages and disadvantages. For surveys of physician practices (or other organizations that employ physicians), there have been no files that are obvious choices to serve as the basis for a sample frame. Here we discuss data collection on physician practices from an analytic perspective and consider how sampling physicians to obtain practice level data may be a desirable approach.